2016
DOI: 10.1080/09540121.2016.1164804
|View full text |Cite
|
Sign up to set email alerts
|

Test and treat: the early experiences in a clinic serving women at high risk of HIV infection in Kampala

Abstract: At the end of 2013, the Government of Uganda issued guidance recommending provision of AntiRetroviral Treatment (ART) to HIV-positive people in key populations, including female sex workers, regardless of CD4 cell count. We describe the implementation of this new guidance in a clinic serving women at high risk of HIV infection in Kampala. Between July and December 2015, we conducted repeat in-depth interviews with 15 women attending the clinic after the change in guidelines, to explore their perceptions regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 22 publications
2
29
0
1
Order By: Relevance
“…Besides characterizing the trial populations with standard socio‐demographic information, these trials also collect experiences and perceptions of a sample of trial participants, community members and services providers. Such qualitative research provides evidence to understand the acceptability of the UTT strategies by the general population 29, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69. Overall, the analysis of the various themes addressed within these five trials will contribute to understanding the impact of UTT strategies in various contexts as well as inform the generalization of such a strategy to new contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Besides characterizing the trial populations with standard socio‐demographic information, these trials also collect experiences and perceptions of a sample of trial participants, community members and services providers. Such qualitative research provides evidence to understand the acceptability of the UTT strategies by the general population 29, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69. Overall, the analysis of the various themes addressed within these five trials will contribute to understanding the impact of UTT strategies in various contexts as well as inform the generalization of such a strategy to new contexts.…”
Section: Resultsmentioning
confidence: 99%
“…There remains, however, uncertainty about the long‐term treatment outcomes of rapid ART initiation (Mbonye 2016). Some concerns include insufficient adherence counselling/education; limited time to prepare psychologically for life with HIV and ART (Black 2014; Kim 2016), pill burden due to other concurrent co morbidities or conditions requiring urgent treatment (for example, tuberculosis) (Nachega 2014); and immune reconstitution inflammatory syndrome (IRIS), especially in individuals with advanced disease (CD4 counts < 200 cells/mm³) (Uthman 2015), all of which could impact on morbidity and engagement in care (Hakim 2017).…”
Section: Introductionmentioning
confidence: 99%
“…53 However, the Present's Emergency Plan for AIDS Relief Scientific Advisory Board has provided recommendations regarding "Test and Start" and women's treatment programs have begun to implement "Test and Start". [54][55][56] The recommendations support the implementation of "Test and Start" initially in high volume clinics in urban areas in concert with clinical protocols that prioritize the sickest patients, as well as, provide continued access and retention for those receiving anti-retroviral treatment. Other recommendations include the importance of health care worker training and education and a public health education program for people living with HIV, peer educators, community health workers and differentiated care as part of antiretroviral treatment.…”
mentioning
confidence: 99%
“…In the Uganda program, harmful alcohol consumption was perceived to be a barrier to early antiretroviral treatment due to poor adherence. 55,57 In a high resource setting, a "Test and Start" program has shown that patients who inject drugs are less likely to obtain viral suppression.…”
mentioning
confidence: 99%
See 1 more Smart Citation